Analisis Keberlanjutan Industri Tenun Songket Sidemen di Kecamatan Sidemen Kabupaten Karangasem - Ni Kadek Ayu Smara Tatarini; M. Rudi Irwansyah (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2025)
The Sidemen songket weaving industry represents an important part of Bali’s local cultural heritage, carrying significant economic, social, and environmental values; however, it currently faces various sustainability challenges. This study aims to analyze the factors influencing sustainability and to identify the key driving factors of the Sidemen songket weaving industry in Sidemen District, Karangasem Regency. The theoretical framework is based on the concepts of the creative economy, traditional weaving craftsmanship, and industrial sustainability using the Triple Bottom Line approach, which encompasses economic, social, and environmental dimensions. This research employs a quantitative approach with a descriptive-analytical research design. Data were collected through field observations, questionnaire surveys administered to songket weavers, and supporting documentation. The collected data were analyzed using the Matrix of Cross Impact Multiplications Applied to a Classification (MICMAC) method to identify key sustainability variables within the industry system. The findings reveal that artisans’ income, environmental awareness, and cultural awareness are the key variables with the strongest influence on the sustainability of the Sidemen songket weaving industry. In conclusion, the sustainability of the Sidemen songket weaving industry can only be achieved through a balanced integration of economic, social, and environmental aspects, supported by the active roles of artisans, the local community, and sustainable government policie.